(8x+6)+(x+5)=

Simple and best practice solution for (8x+6)+(x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+6)+(x+5)= equation:


Simplifying
(8x + 6) + (x + 5) = 0

Reorder the terms:
(6 + 8x) + (x + 5) = 0

Remove parenthesis around (6 + 8x)
6 + 8x + (x + 5) = 0

Reorder the terms:
6 + 8x + (5 + x) = 0

Remove parenthesis around (5 + x)
6 + 8x + 5 + x = 0

Reorder the terms:
6 + 5 + 8x + x = 0

Combine like terms: 6 + 5 = 11
11 + 8x + x = 0

Combine like terms: 8x + x = 9x
11 + 9x = 0

Solving
11 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 9x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 9x = 0 + -11
9x = 0 + -11

Combine like terms: 0 + -11 = -11
9x = -11

Divide each side by '9'.
x = -1.222222222

Simplifying
x = -1.222222222

See similar equations:

| u^2-25= | | y=4mx+2b | | 3u-21= | | y=5mx-7b | | 8w+40= | | 2=-4(1-3j)+3(5j-7) | | w^2+3w-10= | | 2=-4(1-3j)+(5j-7) | | 5n^2+35n=0 | | -19=8(g-3)-5(-3+2g) | | (y^2-11y+30)(5y+10)=0 | | 2(x-2)+15=14 | | 8(n-4)-7(n+8)=-80 | | 15x^2+4xy-4y^2= | | 10x+2x+8x-7x+17(x-1)=43 | | 8(h-4)-7(h+8)=-80 | | 7n^2-20n-32=0 | | 2x^2+3xy-35y^2= | | 2x^2+19xy+35y^2= | | n^2*n^8= | | -7+5x=-42 | | x^3-18x^2+432= | | s^2-2s-63= | | 10+4a=-6 | | 9x^2+81x=0 | | 2m+1=9 | | 12+6x=-54 | | b^2-13b+40=0 | | x^2+18x-225=0 | | 2x^2-6x-55=0 | | 3+4x=-57 | | x^2+18x=225 |

Equations solver categories